(3eNJUQ CHj YhGfgs - (3jYbhH Hf ESMGb Hf EHQGgje GdfjSGHhQqi Ke GdCSaQGjjfj, CHh YhGfI,J (B316 (3g` s
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HHG (B: (3UaI GdMLGH hCfg aQV s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B242s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B453) s
Keywords: (3GdMOjK h GdeUWdMs